Reciprocal regulation of the Epstein-Barr virus BamHI-F promoter by EBNA-1 and an E2F transcription factor. - Sung, N S (1994)
The Epstein-Barr virus BamHI-F promoter (Fp) is one of three used to transcribe the EBNA latency proteins, in particular, EBNA-1, the only viral gene product needed for episomal replication. Fp is distinguished by possession of the only EBNA-1 binding sites (the Q locus) in the Epstein-Barr virus genome outside oriP. Activity of Fp is negatively autoregulated by interaction of EBNA-1 at two sites in the Q locus, which is situated downstream of the RNA start site. We demonstrate in transient assays that this EBNA-1-mediated repression of Fp can be overcome by an E2F transcription factor which interacts with the DNA at a site centered between the two EBNA-1 binding sites within the Q locus. An E2F-1 fusion protein protects the sequence 5'-GGATGGCGGGTAATA-3' from DNase I digestion, and a DNA probe containing this sequence binds an E2F-specific protein complex from cell extracts, although this region is only loosely homologous with known consensus binding sites for E2F transcription factors. In mobility shift assays, E2F can displace the binding of EBNA-1 from the Q locus but not from oriP, where the E2F binding site is not present. E2F also activates expression of Fp in epithelial cells. These findings identify a potentially new binding site for members of the E2F family of transcription factors and suggest that such a factor is important for expression of EBNA-1 in lymphoid and epithelial cells by displacing EBNA-1 from the Q locus. In addition, the possibility that Fp activity is under cell cycle control is raised. Since the supply of functional E2F varies during the cell cycle and since in these assays overexpression of E2F can overcome repression of Fp by EBNA-1, control of transcription of EBNA-1 mRNA by cell cycle regulatory factors may help to bring about ordered replication of episomes.